2013
DOI: 10.1021/nl4016254
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Trapping in Two-Dimensional Nanoscale Plasmonic Optical Lattice

Abstract: We report the transport and trapping behavior of 100 and 500 nm diameter nanospheres in a plasmon-enhanced two-dimensional optical lattice. An optical potential is created by a two-dimensional square lattice of gold nanostructures, illuminated by a Gaussian beam to excite plasmon resonance. The nanoparticles can be guided, trapped, and arranged using this optical potential. Stacking of 500 nm nanospheres into a predominantly hexagonal closed pack crystalline structure under such a potential is also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 47 publications
7
69
0
Order By: Relevance
“…20 A fiber-coupled diode laser 980 nm beam (PL980P330J) was expanded via beam expansion, and loosely focused using an oil immersion microscope objective (NA ¼ 1.25, 100Â, Nikon) to excite the plasmonic sample. The loose focusing was achieved by partially overfilling the back aperture of the microscope objective.…”
Section: A Optical Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…20 A fiber-coupled diode laser 980 nm beam (PL980P330J) was expanded via beam expansion, and loosely focused using an oil immersion microscope objective (NA ¼ 1.25, 100Â, Nikon) to excite the plasmonic sample. The loose focusing was achieved by partially overfilling the back aperture of the microscope objective.…”
Section: A Optical Setupmentioning
confidence: 99%
“…17,18 A scaled-down version of such periodic potentials can be produced using periodic plasmonic nanostructures. 19,20 Cuche et al recently demonstrated that near-field optical forces can produce negative refraction effects on the trajectory of nanoparticles in a plasmonic crystal created in a patterned metallic film. 19 The same group of authors also reported on trapping and transport over a periodic array of gold nanodiscs, under illumination with a loosely Note: Paper submitted as part of the selected papers from the 5th International Conference on Optofluidics (Guest Editors: Shih-Kang Fan and Zhenchuan Yang) held in Taipei, Taiwan, July [26][27][28][29]2015.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, surface plasmons (SPs) excited on a metal film are interesting: through their strong amplitude and phase gradients, they give rise to very efficient momentum transfers enabling direct object manipulations together with pulling effects that maintain particles in the near field [20][21][22][23][24][25]. But while SPs are characterized by chirality flows due to their intrinsic spinning nature, plasmonic chiral densities identically vanish because of the transverse magnetic polarization of SPs [26].…”
Section: Introductionmentioning
confidence: 99%